Impact of Seniors Centers on oral health-related quality of life of older adults - Fernanda W. Machado Luz; Alexandre Emídio Ribeiro Silva; Ana Paula Perroni; Marília L. Goettems; Noéli Boscato (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE This study evaluated the oral health-related quality of life (OHRQoL) of older adults participating or not in Seniors Centers (SC). METHODS Two independent samples were compared: older adults who participate in SC (n = 124) and older adults who visited Primary Healthcare Centers (PHC) and do not participate in SC (n = 164). The data collected consisted of sociodemographic (sex, age, educational level, marital status, family income) and psychosocial characteristics-Sense of Coherence (SOC), anxiety and depression using HADS, happiness-, and oral clinical evaluation-use and need of dental prosthesis and decayed (D), missing (M), or filled (F) teeth. The resulting OHRQoL was evaluated using the Oral Health Impact Profile (OHIP-14). The Mann-Whitney test was used to assess the associations between the independent variables and the OHIP-14. Poisson regression models were also used in the analyses (α=0.05). RESULTS In the PHC, of the 270 individuals invited to participate in the study, 164 (60.7%) were interviewed and clinically examined; while in the SC, of the 166 individuals invited to participate in the study, 124 (74.7%) were interviewed and clinically examined. After adjustments for sociodemographic, psychosocial and clinical factors, we found that the impact on OHRQoL was 2.8 times higher (95%CI 2.0-4.2) for older adults who did not participate in SC. CONCLUSION Older adults who participated in SC showed better perception on OHRQoL, independently of sociodemographic, psychosocial and clinical factors.